Rice Bacterial Blight in Togo: Importance of the Disease and Virulence of the Pathogen - Dewa, K.M.K.; Banito, A.; Onasanya, A.; Kpémoua, K.E.; Sere, Y. (Science Alert, 2011)
Bacterial blight, caused by Xanthomonas oryzae pv. oryzae, is new in Togo. A bacterial blight survey was carried out in the dry savanna and wet savanna zones in the Northern part of Togo revealed its distribution, incidence, severity and virulence of the bacterial strains. Presence of bacterial blight of rice in dry savanna and wet savanna zones was confirmed in 30% of the sites visited. The disease was more frequently found in the dry savanna zone than in the wet savanna zone. High incidence (45%) and severity (50%) of bacterial blight was especially found in the dry savanna zone closer to Burkina Faso. Eleven bacterial strains were isolated from the infected sites and were pathologically characterized by testing their virulence on the rice variety IR841 which is widely grown in Togo. Severity of between 63-90% obtained among strains revealed their highly virulent status and this first record the occurrence of bacterial blight, Xanthomonas oryzae pv. oryzae, in Togo.